(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The article reconstructs the institutional and patrimonial history of Santa Maria of Pomposa between the second half of the 9th and the beginning of the 11th century, i.e. in the first phase of its existence attested by written sources. At the beginning of this period Pomposa seems to have been one of the many monasteria - in all probability simple churches - present in the exarchate, and was characterised by a land patrimony of local dimension and by its inclusion in the power network through which the archbishop of Ravenna governed the exarchate. Only in 986 do we have documentary proof that Pomposa had become a regular monastery, with its own community of monks. But the great transformation occurred a few years later, in 1001, when Otto III elevated Pomposa to the rank of imperial abbey as part of a complex project to establish direct royal control in the Delta area, which included the parallel foundation of the monastery of St. Adalbert in Pereo. The transformation of Pomposa into an imperial abbey can thus be included in the broader action of restoring ecclesiastical and monastic property to royal control ordered by Otto III starting from the Capitulare Ticinense, and thus became a fully integrated action in the concrete policy that gave substance to the Renovatio imperii Romanorum.